Institutional Quality, Trade Openness, and Financial Sector Development in Asia: An Empirical Investigation - Thai-ha Le; Jungsuk Kim; Minsoo Lee (Asian Development Bank (ADB), 2015)
We examine the determinants of financial development in Asia and the Pacific from 1995 to 2011. To do so, we apply the dynamic generalized method of moments to a panel data set of 26 economies in the region. We find that better governance and institutional quality foster financial development in developing economies while economic growth and trade openness are key determinants of financial depth in developed economies.
hdl:11540/5157
Keywords: G10; G20; 330; Asia and the Pacific; economic growth; financial development; governance and institutionalquality; panel data analysis; trade openness